When the city teaches: public art as a tool for educational inclusion - Kumm, Rosely (Revista do Colóquio, 2025)
Aiming at the best development and appreciation of human beings from different social perspectives, this research is part of a context of study and reflection on the possibilities of learning and inclusion, especially regarding the perceptive experience of people with disabilities in relation to public art and local culture. In view of this, adapted and multisensory educational art proposals were developed, which propose an integrated approach to sensory perceptions as essential elements in the construction of artistic knowledge, to be experienced with the public of users of APAE in the municipality of Domingos Martins. The research is part of the studies carried out at the Laboratory of Extension and Research in Arts – LEENA/UFES, on public art in Espírito Santo, which extends to a case study, combining participant observation and interviews with APAE users.